A Pilot Study on the Effectiveness of Platelet-Rich Plasma and Debridement for the Treatment of Nonhealing Fistulas in Spinal Cord–Injured Patients. (March 2015) - Biglari, Bahram; Reitzel, Tim; Swing;, Tyler; Büchler, Axel; Gerner, Hans Jürgen; Schmidmaier, Gerhard; Moghaddam, Arash
ABSTRACT: OBJECTIVES: To determine the effectiveness of platelet-rich plasma (PRP) in the treatment of nonhealing fistula in spinal cord–injured patients. STUDY DESIGN: This was a pilot study of 15 spinal cord–injured patients with chronic pressure ulcers (PrUs) and nonhealing fistulas treated with PRP. SETTING: Germany, Rheinland Pfalz, BG Trauma Center Ludwigshafen METHODS: The authors treated 15 patients with PRP who had nonhealing fistulas due to multiple surgical closures of PrUs. According to the National Pressure Ulcer Advisory Panel's stages, 12 patients had Stage III PrUs, and 3 patients had Stage IV PrUs. RESULTS: After 1 week of treatment with PRP, the authors observed low levels of secretion from the fistulas. After 2 weeks, they noted no further secretion from the fistulas. A magnetic resonance imaging control investigation after 3 weeks showed the complete disappearance of the fistulas. No negative effects and no allergic reactions were noted in the use of PRP. CONCLUSION: The authors' results suggest that the application of PRP in combination with debridement is an effective therapy option and good alternative to recurrent surgical interventions for treating nonhealing fistulas resulting from the surgical closure of PrUs.